Prognostic importance of vascular endothelial growth factor and its receptors in the uterine sarcoma. Issue 2 (1st February 2005) - Arita, S.; Kikkawa, F.; Kajiyama, H.; Shibata, K.; Kawai, M.; Mizuno, K.; Nagasaka, T.; Ino, K.; Nomura, S.
Abstract : Vascular endothelial growth factor (VEGF) and its receptors play an important role in tumor progression; however, there is no report regarding this factor in uterine sarcoma. Thirty-nine patients with uterine sarcoma, 14 carcinosarcomas, 4 endometrial stromal sarcomas, and 21 leiomyosarcomas, were studied. By immunohistochemical staining, VEGF was not detected in normal uterine smooth muscle, but VEGF receptor-1 (flt-1) and VEGF receptor-2 (flk-1) were observed in 14 and 4 of 14 normal smooth muscles, respectively. Of 39 sarcomas, 25 expressed VEGF, and 38 and 34 sarcomas expressed flt-1 and flk-1 at various intensities, respectively. The staining intensity of VEGF, flt-1, and flk-1 was significantly higher in sarcoma than in normal uterine smooth muscle, but that of phospho-flt-1 (p-flt-1) was significantly lower in sarcoma than in normal uterine smooth muscle. When sarcomas were divided into two groups according to staining intensity, a significant difference in survival curves was observed in only p-flt-1 of leiomyosarcoma ( P = 0.008), and in all sarcomas, a lower survival curve was also observed in the high staining intensity group than in the low staining intensity group, although there was no significant difference ( P = 0.102). In conclusion, VEGF and its receptors are suggested to be involved in progression of uterine sarcoma, but only the p-flt-1 level significantly affected the survival of leiomyosarcoma patients.